Arthroscopic Management of Posterior Elbow Impingement - Melissa L. Carpenter BS; Jose F. Vega MD; Cameron Gerhold BS; Michael J. Murray BS; Trevor A. Poulson MS; Nikhil N. Verma MD (Video Journal of Sports Medicine)
Background: Posterior elbow impingement is often seen in athletes who engage in overhead sports that involve repetitive elbow extension; for these patients with persistent symptoms, arthroscopic debridement is often recommended. While traditionally performed in the supine or prone position, arthroscopic elbow debridement performed in the lateral decubitus position has distinct advantages that make it our preferred method. Indications: Arthroscopic debridement in the context of posterior elbow impingement is utilized when conservative management with rest, physical therapy, and nonsteroidal anti-inflammatory drugs (NSAIDs) does not provide improvement in pain or range of motion. Technique Description: After induction of general anesthesia and placement of an interscalene block, the patient is placed on the operating table in the lateral decubitus position utilizing the arm holder of choice. The bony landmarks of the operative elbow are identified, and the joint capsule is insufflated with 25 mL of saline before placement of the arthroscopic portals. A diagnostic arthroscopy of the anterior and posterior compartments of the elbow is first performed. Debridement of loose bodies, inflammatory synovium, and capsular tissue is conducted as needed. Attention is then turned to the direct posterior working portal where the olecranon tip is identified. The posterior olecranon and olecranon fossa are thoroughly smoothed with a shaver to create a flush surface. Scope instrumentation is withdrawn, and the elbow is manipulated to ensure full range of motion. Results: It is the senior author’s belief that management of posterior elbow impingement with arthroscopic debridement in the lateral decubitus approach provides enhanced visualization and allows free manipulation of the joint throughout the procedure. This facilitates direct treatment of the olecranon and olecranon fossa while permitting comprehensive evaluation of the joint for concomitant loose bodies and inflammatory synovium. Additionally, the risk of iatrogenic injury to nearby neurovascular structures while instrumenting the joint is diminished. Discussion/Conclusion: Arthroscopic debridement for posterior elbow impingement in the lateral decubitus position with the operative extremity supported proximally in an arm holder has been shown to optimize arthroscopic viewing of the joint. This technique also provides ease of access to the posterior compartment, thereby substantially and immediately increasing patient range of motion. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.